Development of student mental health scale - Ghinaya Ummul Mukminin; Krisbandaru Hayuningtyas; Daniela Pauleta Naomi; Aulia Azmi Izzatulhaq; Asriani Cahya Fitria; Siti Chotidjah; Lira Fessia Damaianti; Heli Ihsan; Farhan Zakariyya; Wida Widiyani Putri (Himpunan Pengembang Kurikulum Indonesia, 2024)
Mental health among high school (SMA) students is an important issue that needs attention. This research aims to develop a mental health scale for high school students, which is expected to be able to detect whether students have mental problems or not, so that students with problems can get fast and appropriate help. Apart from that, this scale is also expected to be able to see the extent to which students' mental development is good. This scale was developed based on three dimensions of mental health, namely peace with oneself, social interaction function, and basic and advanced psychological needs. The research method employed in this study is the quantitative method. Meanwhile the participants involved in this research were 1045 high school students consisting of students in grades 10-12. The analysis technique uses item-total correlation and exploratory factor analysis. The result was that 25 items had satisfactory item-total correlations with values ranging from 0.307 to 0.677. The results of the exploratory factor analysis that has been carried out are the formation of three dimensions with a different distribution of items from the initial design. Apart from that, this measuring tool also has a cumulative proportion of variance explained by factors of 0.434 and a model fit of CFI (0.910) and TLI (0.900). In the future, in-depth research is needed regarding the external validity of this mental health scale, which is correlated with other variables using convergent and discriminant validity methods. Abstrak Kesehatan mental pada siswa Sekolah Menengah Atas (SMA) merupakan salah satu permasalahan penting yang perlu menjadi perhatian. Penelitian ini bertujuan untuk mengembangkan alat ukur kesehatan mental bagi siswa SMA, yang diharapkan dapat mendeteksi apakah siswa memiliki permasalahan mental atau tidak, sehingga siswa yang bermasalah bisa mendapatkan pertolongan yang cepat dan tepat. Selain itu, alat ukur ini juga diharapkan dapat melihat sejauh mana mental siswa berkembang dengan baik. Skala ini dikembangkan berdasarkan tiga dimensi kesehatan mental yaitu berdamai dengan diri sendiri, fungsi interaksi sosial, serta kebutuhan psikologis dasar dan lanjut. Metode penelitian yang digunakan dalam penelitian ini adalah metode kuantitaif, sedangkan partisipan yang terlibat dalam penelitian ini sebanyak 1045 siswa SMA terdiri dari siswa kelas 10-12. Teknis analisis menggunakan korelasi item-total dan analisis faktor eksploratori. Hasilnya 25 item memiliki korelasi item-total yang memuaskan dengan nilai antara 0.307 sampai 0.677. Hasil dari analisis faktor eksploratori yaitu terbentuknya tiga dimensi dengan sebaran item yang berbeda dari rancangan awal, selain itu alat ukur ini juga memiliki proporsi kumulatif varian yang dijelaskan oleh faktor sebesar 0.434 dan model fit CFI (0.910) dan TLI (0.900). Untuk selanjutnya, perlu penelitian mendalam mengenai validitas eksternal skala kesehatan mental ini yang dikorelasikan dengan variabel-variabel lain menggunakan metode validitas konvergen dan diskriminan. Kata Kunci: Evaluasi; kesehatan mental; siswa SMA; pengembangan alat ukur